PLANIFICACIÓN ESTRATÉGICA PARA LA COMPAÑÍA DE TRANSPORTE ESCOLAR ENTRE RÍOS S.A. PERÍODO 2019 – 2023 - Castro Iriarte, Jenny Maritza (2019)
This thesis work called "STRATEGIC PLANNING FOR THE COMPANY OF TRANSPORT ESCOLAR BETWEEN RIOS S.A. PERIOD 2019 – 2023" aims to contribute with alternative plans and tools, which contribute in strengthening and growth institutional goals to achieve the objectives and goals. For the development of this work, scientific, deductive, inductive and analytical methods were applied, applying fieldwork techniques such as direct observation, interview, surveys and bibliographic review that allowed to obtain necessary information to develop the procedures involved in strategic planning. To meet the objectives, it began with an analysis of the current situation of transport in the city of Loja to learn how its infrastructure is located, the different cooperatives and transport companies involved in this sector, as well as the different modes of transport offered by the service at the local level. In the second objective, a situational diagnosis was developed based on the information provided by the managers where it was possible to know how the company is structured and through direct observation the veracity of the information was corroded. In the third objective, an internal analysis was carried out that identified the strengths among them are that it has its own headquarters and has a modern vehicle fleet, within the weaknesses are the lack of a strategic plan and lack of publicity; external analysis identified ministerial agreements as an opportunity and the main threat to illegal competition, based on these factors the FODA matrix (strengths, weaknesses, opportunities and threats) was developed. Finally, the objectives and strategies are also set out the activities, budget, schedule for each objective in such a way that they are met methodically under the established requirements, as well as a matrix for the evaluation of strategies at the completion of the strategic plan, thus enabling the fourth objective to be achieved. With the results obtained it is concluded that the company enjoys a good positioning within the school transport sector, the MEFI and MEFE matrices have a weighted average of 2.69 and 2.86 respectively, in this context the company is taking advantage of its mitigating weaknesses also takes advantage of existing opportunities and minimizes potential negative effects of threats.